Elemental composition of the rice plant as affected by iron toxicity under field conditions - Sahrawat, K.L. (Informa UK Limited, 2000)
Iron (Fe) toxicity is a major nutrient disorder affecting the production of wetland rice in the humid zone of West Africa. Little attention has been given to determining the macro‐ and micronutrient composition of rice plants grown on wetland soils where Fe toxicity is present although results from such study could provide useful information about the involvement of other nutrients in the occurrence of Fe toxicity. A field experiment was conducted in the 1997 dry season (January‐May) at an Fe toxic site in Korhogo, Ivory Coast, to determine the elemental composition of Fe tolerant (CK 4) and susceptible (Bouake 189) lowland rice varieties without and with application of nitrogen (N), phosphorus (P), potassium (K), and zinc (Zn). For both Fe‐tolerant and susceptible varieties, there were no differences in elemental composition of the whole plant rice tops, sampled at 30 and 60 days after transplanting rice seedlings, except for Fe. All the other nutrient element concentrations were adequate. Both Fe‐tolerant and susceptible cultivars had a high Fe content, well above the critical limit (300 mg Fe kg‐1 plant dry wt). These results along with our observations on the elemental composition of rice plant samples collected from several wetland swamp soils with Fe toxicity in West Africa suggest that “real”; iron toxicity is a single nutrient (Fe) toxicity and not a multiple nutrient deficiency stress.